Ответ:
6
Пошаговое объяснение:
3/4 * 1/6х - 3/4 * 1/3 = 2х - 11. 1/2
3/24х - 3/12 = 2х - 11. 1/2
3/24х - 2х = -11. 1/2 + 3/12
3/24х - 1. 24/24х = -11. 6/12 + 3/12
-1. 21/24х = -11. 3/12
-1. 7/8х = -11. 1/4
-15/8х = -45/4
х = -45/4 : (-15/8)
х = -45/4 * (-8/15)
х = -3/1 * (-2/1)
х = 6/1
х = 6
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
6
Пошаговое объяснение:
3/4 * 1/6х - 3/4 * 1/3 = 2х - 11. 1/2
3/24х - 3/12 = 2х - 11. 1/2
3/24х - 2х = -11. 1/2 + 3/12
3/24х - 1. 24/24х = -11. 6/12 + 3/12
-1. 21/24х = -11. 3/12
-1. 7/8х = -11. 1/4
-15/8х = -45/4
х = -45/4 : (-15/8)
х = -45/4 * (-8/15)
х = -3/1 * (-2/1)
х = 6/1
х = 6